2015
DOI: 10.15414/afz.2015.18.si.43-44
|View full text |Cite
|
Sign up to set email alerts
|

Textural properties of spelt noodles

Abstract: The texture of cooked noodles is a very important quality characteristic for both processors and consumers. Selected indicators of noodle texture of three spelt cultivars-Altgold, Ostro and Franckenkorn grown in an ecological system during the years 2010-2011 are presented. A TA.XT Plus (texture analyzer) was used to determine cooked spelt wheat noodle firmness, hardness, adhesiveness, elasticity and extensibility, following AACC (66-50) standard method. The spelt wheat noodle texture quality was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A comparative study with spelt varieties showed acceptable sensory scores with significant differences among the varieties (Korczyk Szabó and Lacko Bartošová ), leading to conclude that spelt might be a suitable raw material for bread making, but it remains closely related to the choice of spelt variety (Korczyk Szabó and Lacko Bartošová ). Compared to common bread, spelt genotypes had high crumb elasticity, but low crumb cell homogeneity, which are probably due to its special dough rheological attributes (Callejo and others ).…”
Section: Ancient Grains‐based Foodstuffs: Nutritional Added Value Andmentioning
confidence: 99%
“…A comparative study with spelt varieties showed acceptable sensory scores with significant differences among the varieties (Korczyk Szabó and Lacko Bartošová ), leading to conclude that spelt might be a suitable raw material for bread making, but it remains closely related to the choice of spelt variety (Korczyk Szabó and Lacko Bartošová ). Compared to common bread, spelt genotypes had high crumb elasticity, but low crumb cell homogeneity, which are probably due to its special dough rheological attributes (Callejo and others ).…”
Section: Ancient Grains‐based Foodstuffs: Nutritional Added Value Andmentioning
confidence: 99%